ANALISIS DAN PERANCANGAN SISTEM INFORMASI GEOGRAFIS PEMETAAN PENGGUNA NARKOTIKA DI WILAYAH PULAU JAWA PASCA PANDEMI - Bambang Agus Herlambang; Ainia Hasna Salsabila (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The COVID-19 pandemic has had a significant impact on various aspects of life, including an increase in cases of drug abuse. This research aims to design a Geographic Information System (GIS) that is capable of accurately and visually mapping the distribution of drug users in the Java Island region after the pandemic. It is hoped that this GIS can become a tool for policy makers, law enforcers and other related parties in efforts to prevent and overcome drug problems. The methods used in this research include collecting non-spatial data analysis and spatial data analysis, as well as designing a web-based system. The data used includes demographic data as well as data on drug abuse cases. Spatial analysis was carried out to identify distribution patterns of drug users and the factors that influence them. The results of this research are a web-based information system that is capable of displaying interactive maps of the distribution of drug users, as well as providing various spatial analysis features It is hoped that this GIS can make a significant contribution in efforts to reduce the number of drug abuse on the island of Java by providing accurate and up-to-date information regarding the situation in the field.